THE EFFECT OF READING, QUESTIONING, AND ANSWERING (RQA) STRATEGY WITH PROBLEM BASED LEARNING MODEL TO IMPROVE STUDENTS’ HOTS SCIENCE LITERACY ABILITY ON THERMOCHEMISTRY - Vincencia Friandini Sagala; Iis Siti Jahro (UNESA Journal of Chemical Education, 2026)
This research aims to determine the effect of integrating the Reading, Questioning, and Answering (RQA) strategy with the Problem-Based Learning (PBL) model in improving students' Higher-Order Thinking Skills (HOTS) and science literacy in thermochemistry. The background of this research is the low science literacy and critical thinking skills of students, as evidenced by Indonesia's low scores in international assessments such as PISA and TIMSS. This study uses a quantitative method with a pre- experimental one-group pretest-posttest design on 11th-grade science students. The research instrument is a 20-item multiple-choice test validated to measure three HOTS cognitive levels (Analyzing, Evaluating, Creating) and nine science literacy indicators. The results showed a significant improvement in learning outcomes (p < 0.001), with the average pretest score of 34.84 increasing to 68.87 in the posttest. The Normalized gain (N-Gain) value is 0.52, falling into the moderate category. The analysis also showed a significant increase in students' understanding; for example, the ability to distinguish scientifically investigable questions increased from 0% to 70.97%. Despite improvements in analytical and evaluative skills, students continue to struggle with mathematical calculations related to quantitative data. In general, the combination of RQA and PBL methods is effective in helping students understand the material through independent reading and questioning before class, thereby enhancing their readiness to critically address real-world problems in the classroom.